OVERVIEW OF SMART CITY POLICY IMPLEMENTATION: A NEW APPROACH TO JAMBI CITY GOVERNMENT ADMINISTRATION IN THE INDUSTRY 4.0 ERA. - Maulana, Rio Yusri; Yanti, Ovie; Sukmawati, Nur (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
Industry 4.0 provides technological mastery opportunities as a key to determine of national competitiveness. In line with this, the government needs to build integrated information and communication technology (e-government) services aimed at supporting the realization of the concept. Therefore, the government has legalized a regulation relating to information technology. One of the programs implemented by Ministry of Communication and Information, Ministry of Home Affairs, Ministry of Public Works & Housing (PUPR), National Development Planning Agency (Bappenas) and the Presidential Staff Office is the Movement Towards 100 Smart Cities which is a joint program of the ministry. The program aims to guide districts / cities in formulating Smart City Master Plans in order to further maximize the use of technology, both in improving community services and accelerating the potential that exists in each region. This study aims to determine the implementation of the Smart City program in the City of Jambi, the innovations that have been implemented, as well as the obstacles and challenges faced in the implementation of the program in the industry 4.0. This study uses a qualitative approach carried out in the city of Jambi. From the results, the implementation of the smart city program began with the Preparation of the Smart City Master Plan of Jambi City in 2014, then the implementation of the development of smart cities that began in 2017 and is still ongoing (2020). To support the implementation of the City of Jambi City smart city program which already has 50 technological innovation applications to support the performance of the Jambi City Government and facilitate the service process to the community. In its application there are various obstacles and challenges such as limited financial resources and limited human resources in the field of information technology, because not all OPD have experts in the IT field